A Novel Passive Shoulder Exoskeleton Using Link Chains and Magnetic Spring Joints - Lee, Hyun Ho; Yoon, Kyung Taek; Lim, Hyun Ho; Lee, Won Kyu; Jung, Jae Hwan; Kim, Seung Beom; Choi, Young Man (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2024)
Work-related musculoskeletal disorders represent a major occupational disability issue, and 53.4% of these disorders occur in the back or shoulders. Various types of passive shoulder exoskeletons have been introduced to support the weight of the upper arm and work tools during overhead work, thereby preventing injuries and improving the work environment. The general passive shoulder exoskeleton is constructed with rigid links and joints to implement shoulder rotation, but there exists a challenge to align with the flexible joint movements of the human shoulder. Also, a force-generating part using mechanical springs require additional mechanical components to generate torque similar to the shoulder joint, resulting in increased overall volume and inertia to the upper arm. In this study, we propose a new type of passive shoulder exoskeleton that uses magnetic spring joint and link chain. The redundant degrees of freedom in the link chains enables to follow the shoulder joint movement in the horizontal direction, and the magnetic spring joint generates torque without additional parts in a compact form. Conventional exoskeletons experience a loss in the assisting torque when the center of shoulder rotation changed during arm elevation. Our exoskeleton minimizes the torque loss by customizing the installation height and initial angle of the magnetic spring joint. The performances of the proposed exoskeleton were verified by an electromyographic evaluation of shoulder-related muscles in overhead work and box lifting task.
Keywords: Arm; Exoskeleton; Gravity compensation; Link chain; Magnetic spring; Scapulohumeral rhythms; Shoulder; Spring joints; Upper arm; Biomechanical Phenomena; Electromyography; Exoskeleton Device; Humans; Magnetic Phenomena; Shoulder; Upper Extremity; electromyography; Exoskeleton; gravity compensation; link chains; magnetic spring; scapulohumeral rhythm